Rosacea-like skin reaction under treatment with dupilumab for atopic dermatitis - C. Grote; F. Zirkenbach; J. N. Wagner; M. Augustin (Journal of Dermatological Treatment)
Purpose Dupilumab is a widely recommended treatment for moderate-to-severe atopic dermatitis (AD), with known ocular side effects but less frequent cutaneous reactions.Material and methods This case report details a 52-year-old female patient with atopic dermatitis treated with dupilumab. After an initially successful treatment, the patient developed a rosacea-like dermatitis. At first, dupilumab was continued alongside doxycycline, metronidazole gel and ivermectin cream.Results Following a worsening of her skin condition, dupilumab was discontinued. Lebrikizumab was introduced, leading to significant regression of the lesions.Conclusions This case highlights a rare paradoxical skin reaction to dupilumab, potentially linked to the blockade of IL-4Rα, which may shift the immune response towards a Th1/Th17 phenotype. The findings suggest that alternative therapies, such as IL-13 inhibitors, should be considered when cutaneous side effects arise during dupilumab treatment.